Management accounting change as an amplifier of a leadership dispute: an ethnography of convergent and divergent leader-follower relations - Bassani Gaia; Pfister Jan A.; Cattaneo Cristiana (Emerald, 2025)
Purpose
The purpose of this paper is to explore the role of leadership in management accounting change processes and outcomes.
Design/methodology/approach
The paper draws on an ethnographic study in a Southern European company and mobilizes leader–follower relations as a method theory to analyse the observations.
Findings
The findings show how a leadership dispute between two top managers can be amplified during the management accounting change process and percolate throughout an organization. The authors identify five contested areas where the role of accounting amplifies the leadership dispute by unfolding its reach to other organizational actors. The leadership dispute can shape and reinforce a fragmented organization, with some organizational members creating convergent leader–follower relations while others divert and fragment with an increased turnover. This amplification can lead to unexpected outcomes of the change process in terms of how and by whom accounting is performed.
Research limitations/implications
The authors propose the study of leadership and followership as an important but, to date, largely neglected theme in management accounting research.
Originality/value
In contrast to the prior management accounting literature, the paper departs from a leadership-centric and role-based approach and employs a co-constructionist and relational approach to leadership and followership to analyse management accounting change. In addition, it applies and extends Alvesson's (2019a) theory on “divergent relationalities” between the presumed leaders and followers. In doing so, the paper also adds to the leadership field by theorizing and integrating the situation of a leadership dispute in this novel theoretical framework.
Keywords
Management accounting change, Leadership, Followership, Disputes, Divergent relationalities, Ethnography